Midline Household Survey Results: Bagerhat, Bangladesh - Hossain, Emdad; Rashid, Harun Or; Aggarwal, Roopali; Nagpal, Mansi; Khatri-Chhetri, Arun (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The CGIAR Research Program on Climate Change, Agriculture and Food Security, with the collaboration of WorldFish Bangladesh, carried out the household midline surveys in 2019 in the Morrelganj Upazila area of the Bagherhat district, Khulna division. A total of 140 household surveys were administered in 7 villages, namely Gabgachhia, Chak Vatkhali, Uttar Sutalori, Chak Putikhali, Dharadoha, Gazalia and Borshibaoa. The survey was conducted using the open data kit (ODK) on Android devices, in this case smartphones and tablets. The household questionnaire was translated into the local language, Bangla, and the field enumerators were trained for a week in July 2019. The questionnaires were then field- tested to assess the adequacy of the language used and to further develop the capacities of the enumerators. The regional team leader and the on-site team leader monitored the field survey activities and checked the quality of data regularly. The midline survey gathered information at the household-level on agricultural practices, changes made on those over time and in particular since the baseline, sources of weather, climate and agriculture related information, livelihood/agriculture/natural resource management strategies pursued and the current risk management, mitigation and adaptation practices adopted. The survey also collected information on each household’s demography and characteristics, including asset ownership and livelihood type.